DIFFERENSIAL TRADISI PETIK LAUT KLASIK DAN MODERN DI PULAU GILI GENTING KABUPATEN SUMENEP MADURA - Dinanti, Syintia Dwi; Ismiyana, Ulydhatul (HUNAFA Jurnal Studia Islamika, 2023)
The aim of this research is to find out the different cultures of the classical and modern sea picking traditions on Gili Genting Island, Madura. The research method used is a comparative study by comparing the sea-picking rituals of Hindus and Muslims. Research data collection techniques used include observation, interviews, secondary data collection, and literacy studies carried out using purposive sampling. Interviews were carried out by asking in-depth open questions as well as giving questionnaires. Then, secondary data was obtained by studying literature from related research. Research results: The core ritual of the sea-picking tradition is a form of shifting cultural values that is adapted to the diversity of local communities or is called the differentiation of classical and modern sea-picking traditions. This can be understood as a development of religious knowledge in society and a form of openness of coastal communities to the religious teachings they adhere to.